Age Does Not Affect Metoprolol's Effect on Perioperative Outcomes (From the POISE Database). (April 2018) - Jacka, Michael J.; Guyatt, Gordon; Mizera, Richard; Van Vlymen, Janet; Ponce de Leon, Dario; Schricker, Thomas; Bahari, Mohd Yani; Lv, Bonan; Afzal, Lalitha; Plou García, Maria Pilar; Wu, Xinmin; Nigro Maia, Lília; et al.
Abstract : BACKGROUND: Perioperative β-blockade reduces the incidence of myocardial infarction but increases that of death, stroke, and hypotension. The elderly may experience few benefits but more harms associated with β-blockade due to a normal effect of aging, that of a reduced resting heart rate. The tested hypothesis was that the effect of perioperative β-blockade is more significant with increasing age. METHODS: To determine whether the effect of perioperative β-blockade on the primary composite event, clinically significant hypotension, myocardial infarction, stroke, and death varies with age, we interrogated data from the perioperative ischemia evaluation (POISE) study. The POISE study randomly assigned 8351 patients, aged ≥45 years, in 23 countries, undergoing major noncardiac surgery to either 200 mg metoprolol CR daily or placebo for 30 days. Odds ratios or hazard ratios for time to events, when available, for each of the adverse effects were measured according to decile of age, and interaction term between age and treatment was calculated. No adjustment was made for multiple outcomes. RESULTS: Age was associated with higher incidences of the major outcomes of clinically significant hypotension, myocardial infarction, and death. Age was associated with a minimal reduction in resting heart rate from 84.2 (standard error, 0.63; ages 45–54 years) to 80.9 (standard error, 0.70; ages >85 years; P < .0001). We found no evidence of any interaction between age and study group regarding any of the major outcomes, although the limited sample size does not exclude any but large interactions. CONCLUSIONS: The effect of perioperative β-blockade on the major outcomes studied did not vary with age. Resting heart rate decreases slightly with age. Our data do not support a recommendation for the use of perioperative β-blockade in any age subgroup to achieve benefits but avoid harms. Therefore, current recommendations against the use of β-blockers in high-risk patients undergoing noncardiac surgery apply across all age groups.